Sol–gel silica glass-cladding semiconductor-core optical fiber. (June 2017) - El Hamzaoui, Hicham; Bouwmans, Géraud; Capoen, Bruno; Chen, Na; Douay, Marc; Bouazaoui, Mohamed
Graphical abstract: Highlights: Multi-material optical fiber preforms have been fabricated using the sol–gel technique. The sol–gel clad material efficiently protects the silicon core against ambient gas oxidation, which facilitates the drawing process. After drawing, no dissolution of the cladding glass in the core melt has been observed. The silicon core keeps its composition and polycrystalline structure all along the fabrication process. Abstract: Hybrid optical fibers consisting of glass clad and semiconductor core materials are extensively investigated due to their interesting properties that make them attractive for several technological applications. Here, we report on a new approach for the fabrication of such multi-material optical fiber preform using the sol–gel technique. It consists in mechanically drilling a central hole in a silica xerogel rod, then in filling this hole with a centimeter-length silicon rod, and finally in densifying the silica glass jacket around the silicon core. By drawing this preform, a homogenous hybrid rod-type fiber was obtained. The composition and the structural properties of the pristine silicon rod, of the hybrid preform and of the drawn fiber have been investigated using electron probe microanalysis, Raman spectroscopy and transmission electron microscopy. We have shown that the silicon core material preserves its composition and polycrystalline structure all along the fabrication process.